2023
DOI: 10.3390/nu15071620
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Barrier Dysfunction and Microbiota–Gut–Brain Axis: Possible Implications in the Pathogenesis and Treatment of Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder with multifactorial etiology, characterized by impairment in two main functional areas: (1) communication and social interactions, and (2) skills, interests and activities. ASD patients often suffer from gastrointestinal symptoms associated with dysbiotic states and a “leaky gut.” A key role in the pathogenesis of ASD has been attributed to the gut microbiota, as it influences central nervous system development and neuropsychological and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 216 publications
0
10
0
Order By: Relevance
“…Consequently, disruptions in the gut microbiota could lead to disturbances in neurotransmitter levels, potentially triggering or exacerbating E/I imbalances in individuals with ASD, thereby affecting behavior and emotions. This underscores the vital role of the gut microbiota and neurotransmitters in the pathogenesis of ASD [ 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, disruptions in the gut microbiota could lead to disturbances in neurotransmitter levels, potentially triggering or exacerbating E/I imbalances in individuals with ASD, thereby affecting behavior and emotions. This underscores the vital role of the gut microbiota and neurotransmitters in the pathogenesis of ASD [ 168 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that the ingestion of a probiotic blend (10 10 CFU/day) comprising L. rhamnosus, B. bifidum, L. plantarum LP28, B. longum, Lactobacillus rhamnosis GG, L. lactis over 16 weeks effectively shields dopamine-releasing neurons and consequently mitigates the decline in motor dysfunctions in MitoPark PD mice. A study was conducted to investigate the impact of probiotic Lacticaseibacillus paracasei on motor disorders in rats with PD (Dargenio et al, 2023). The results revealed that the group receiving probiotic L. paracasei exhibited reduced apomorphine rotation test scores compared to the group receiving saline.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Recently, there has been a growing emphasis on investigating the link between autism and the gut–brain axis (GBA). The GBA is a bidirectional communication system between the intestine and the brain, where the intestinal microbiota consisting of bacteria, viruses, archaea, yeasts, and protists in the mucosa plays a crucial role [ 35 ]. In this regard, a significant incidence of gastrointestinal disorders has been identified among children with ASD compared to children with typical development [ 36 ].…”
Section: Introductionmentioning
confidence: 99%